2005
DOI: 10.1074/jbc.m502951200
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Box cis-Element in Human Heavy Ferritin mRNA 5′-Untranslated Region Is a Unique Translation Enhancer That Binds Poly(C)-binding Proteins

Abstract: Intracellular levels of the light (L) and heavy (H) ferritin subunits are regulated by iron at the level of message translation via a modulated interaction between the iron regulatory proteins (IRP1 and IRP2) and a 5-untranslated region. Iron-responsive element (IRE). Here we show that iron and interleukin-1␤ (IL-1␤) act synergistically to increase H-and L-ferritin expression in hepatoma cells. A GC-rich cis-element, the acute box (AB), located downstream of the IRE in the H-ferritin mRNA 5-untranslated region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Under identical conditions, the H-ferritin IRE sequences bound to both IRP1 and IRP2 (Fig. 1D), confirming established RNA gel shift assay data in previous reports (15,26,42). These biotinylated RNA pulldown results showed that APP IRE sequences selectively bound to IRP1 and confirmed the results of our IP-RT-PCR experiments (panel A), showing that that IRP2 did not bind to APP IRE sequences under conditions where IRP2 was readily detected to bind to the canonical H-ferritin IRE (n ϭ 8).…”
Section: Ironsupporting
confidence: 78%
See 1 more Smart Citation
“…Under identical conditions, the H-ferritin IRE sequences bound to both IRP1 and IRP2 (Fig. 1D), confirming established RNA gel shift assay data in previous reports (15,26,42). These biotinylated RNA pulldown results showed that APP IRE sequences selectively bound to IRP1 and confirmed the results of our IP-RT-PCR experiments (panel A), showing that that IRP2 did not bind to APP IRE sequences under conditions where IRP2 was readily detected to bind to the canonical H-ferritin IRE (n ϭ 8).…”
Section: Ironsupporting
confidence: 78%
“…42) for a full method). Supernatants that maintained abundant endogenous mRNAs were used as a positive control for detecting the presence of both H-ferritin and APP RNA under all conditions (Fig.…”
Section: Ironmentioning
confidence: 99%
“…The exact mechanism how this is accomplished is not known yet; however, a recent study suggests that Fe 2ϩ might weaken the IRE-IRP repressor complex in vitro (75). Moreover, it was reported that binding of poly-C binding protein 1 to the acute box cis element within the 5Ј-UTR of the human H-ferritin mRNA facilitates H-ferritin translation when the cytosolic iron concentration is increased (76). These data demonstrate that translational inhibitory RNA elements could be modulated by RNA binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor a (TNFa) stimulates transcription of murine H-ferritin mRNA via NF-kB binding to the enhancer element FER2, located 4.8 kb upstream of the transcription start site (Kwak et al 1995). Other cytokines, such as interleukin 1b (IL-1b) enhance H-ferritin mRNA translation via binding of poly(C)-binding proteins to a GC-rich acute box in the 59 UTR (Thomson et al 2005). Xenobiotics and oxidative stress induce ferritin mRNA transcription via binding of Nrf2/Maf or JunD to antioxidant response elements (AREs) within both H-and L-ferritin genes (Tsuji et al 2000;Hintze and Theil 2005;Tsuji 2005).…”
Section: Introductionmentioning
confidence: 99%